Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages It seems certain that at first there would be a very strong campaign against it, mistresses stirring up maids to opposition, as they did in regard to Health Insurance. But as we have found, when carefully argued out, the domestic worker sees the advantages and changes her view. The women already in insurable trades are unanimously in favour of the extension of the Act to domestic workers, whether working in an institution run for profit or not. 13. Trade Unionism Lack of organisation makes any charter impossible of fulfilment. The domestic workers must be organised before they can make effective changes in the conditions of their employment. Such organisation should be carried out through the efforts of the Unions now catering for large bodies of general workers. We urge upon them the importance of setting up special sections and helping through special campaigns to bring in these workers. In the interests of women now unemployed, and of women in other trades, we hope that this great body of women workers may be brought into close relationship with other workers. Through suitable literature and social clubs lies the simplest approach to these scattered and rather inaccessible workers. By the development of the last proposals of our charter, we believe the problem of organisation will also be helped towards solution. 14. How to Enforce these Conditions of Work We come now to the final problem. With a few exceptions the proposals we made in our pamphlet for Joint Councils have met with agreement. Many industries have Joint Councils* in which representatives of employers and employed meet to draw up agreements as to conditions in the industry. These have not the force of law, but they become the practice of the workers and employers concerned. We want such Coun- * Joint Industrial Councils have been set up in many trades since the War under a scheme proposed by a Committee over which Mr. J.H. Whitley presided, and so are popularly known as "Whitley Councils." (21) 126/TG/RES/X/1036A/7